ARCHITECTING ROBUST INFORMATION FLOWS IN ADVANCED ARTIFICIAL INTELLIGENCE SYSTEMS - Hari Kiran Vuyyuru, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
In the rapidly evolving landscape of generative artificial intelligence, the fundamental infrastructure of data pipelines emerges as a critical determinant of model performance and efficacy. This comprehensive article explores the architectural considerations, methodological approaches, and emerging trends in data pipeline design for AI systems. The article examines how modern pipeline architectures have evolved from basic ETL processes to sophisticated neural highways, incorporating advanced preprocessing methodologies, scalable infrastructure, and seamless machine learning workflow integration. Through analysis of enterprise implementations across various sectors, this study demonstrates how optimized pipeline architectures significantly improve processing efficiency, reduce operational costs, and enhance model performance. The article encompasses quality assessment protocols, adaptive processing algorithms, performance optimization strategies, and the integration of emerging technologies such as edge computing and quantum-inspired algorithms, providing insights into the future direction of data pipeline architecture in AI systems.